Effects of peer versus expert exercise standards on exercise cognitions and behaviour. Issue 11 (1st November 2020) - Magnan, Renee E.; Schmiege, Sarah J.; Klein, William M. P.; Bryan, Angela D.
Abstract: Objective: This experiment examined whether people respond differently to information about where they stand relative to peer behaviour or to expert behavioural recommendations, and whether responses depend on the attainability of these standards. Design: University students (N = 345) were randomly assigned to receive information about their exercise levels relative to peer behaviour or expert recommendations, both varying in attainability, or to a no-feedback control. Main Outcome Measures: Exercise-related cognitions were assessed immediately after feedback and exercise intentions and behaviour were assessed one month later. Results : Among those who received expert recommendations, immediate perceived comparative risk as well as exercise intentions one month later were higher if the standard was more attainable. Those who received peer information reported more exercise minutes in the past week if the standard was less attainable. Conclusion: These outcomes provide evidence that attainability of the standard should be a consideration for norm- and information-based health behaviour interventions.